2014
DOI: 10.1038/ncomms4904
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of Bcl6 is sufficient for oncogenic function and induction of mature B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common lymphoma and can be separated into two subtypes based upon molecular features with similarities to germinal center B-cells (GCB-like) or activated B-cells (ABC-like). Here we identify gain of 3q27.2 as being significantly associated with adverse outcome in DLBCL and linked with the ABC-like subtype. This lesion includes the BCL6 oncogene, but does not alter BCL6 transcript levels or target-gene repression. Separately, we identify expression of BCL6 in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 69 publications
5
65
1
Order By: Relevance
“…In addition to GCB lymphomas, it has been shown that gain-of-function in BCL6 frequently occurs in ABC lymphomas (6), which display a more mature, post-germinal center phenotype. The role of BCL6 in ABC lymphomas remains largely unknown and it is possible that its alteration is required only for initiation of this lymphoma subtype (18), although recent reports indicate that activated B-cell lymphomas may require sustained BCL6 activity (19). As above, KMT2D and CREBBP are frequently mutated in follicular lymphoma and DLBCL and have also been implicated in B-cell maturation specifically via a reduction in CD40L and cytokine responsive transcription (8,9,20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to GCB lymphomas, it has been shown that gain-of-function in BCL6 frequently occurs in ABC lymphomas (6), which display a more mature, post-germinal center phenotype. The role of BCL6 in ABC lymphomas remains largely unknown and it is possible that its alteration is required only for initiation of this lymphoma subtype (18), although recent reports indicate that activated B-cell lymphomas may require sustained BCL6 activity (19). As above, KMT2D and CREBBP are frequently mutated in follicular lymphoma and DLBCL and have also been implicated in B-cell maturation specifically via a reduction in CD40L and cytokine responsive transcription (8,9,20).…”
Section: Introductionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From according to the manufacturer's instructions and analyzed as described previously. 27 For detailed methodology, refer to supplemental Methods. These data have been deposited in the Gene Expression Omnibus (GSE85490).…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…27 Briefly, samples were sectioned, dewaxed, and heated in 10 mmol/L sodium citrate buffer for 30 minutes. Slides were incubated with primary antibodies, including anti-MYC (Clone-Y69; Master Diagnostica, prediluted), anti-Bcl6 (Clone-LN22; Leica Biosystems), and anti-Pax5 (Clone-1EW, Leica Biosystems).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…[4][5][6] Furthermore, expression of several important proteins, such as BCL6, is also regulated by methylation status. 7,8 BCL6 is essential for GCB-cell development, as it is critical to cell proliferation, suppression of the DNA damage response during antibody class switching, and acquisition of somatic hypermutations. 9,10 A high level of BCL6 expression is consistently observed in GCB-DLBCL.…”
Section: Introductionmentioning
confidence: 99%